2021
DOI: 10.1088/1748-9326/ac30f7
|View full text |Cite|
|
Sign up to set email alerts
|

Channeling environmentalism into climate policy: an experimental study of Fridays for Future participants from Germany

Abstract: This study argues that scholars and policy-makers need to understand environmental activists better to bridge the gap between growing activism and policy. Conventional wisdom is that environmental activists generally support stronger climate policies. But there is still little understanding about diversity of views within activist groups when it comes to specific policies, and existing studies indicate that their views are not uniform, which can weaken their impact as a group. Activists might unite to demand c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…Second, we also contribute to a recent stream of literature investigating the motivational (preferences and beliefs) structure underlying climate protest participation. Climate protesters tend to be instrumentally (i. e. to attain a change of public policy) motivated (de Moor et al, 2020;Cologna et al, 2021), although there is regional and individual heterogeneity about advocated means (Beer, 2020;Svensson and Wahlström, 2021;Huttunen, 2021;Soliev et al, 2021), but there is also a strong affectiveemotional basis, revolving around feelings of worry, anxiety, frustration, and anger (Wahlström et al, 2019;de Moor et al, 2020), and a perceived moral duty to act (Fernandes-Jesus et al, 2020;Wallis and Loy, 2021). Social expression and self-signaling, identification, and event enjoyment also play a role (Walgrave et al, 2012;Fernandes-Jesus et al, 2020;Wallis and Loy, 2021;Cologna et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Second, we also contribute to a recent stream of literature investigating the motivational (preferences and beliefs) structure underlying climate protest participation. Climate protesters tend to be instrumentally (i. e. to attain a change of public policy) motivated (de Moor et al, 2020;Cologna et al, 2021), although there is regional and individual heterogeneity about advocated means (Beer, 2020;Svensson and Wahlström, 2021;Huttunen, 2021;Soliev et al, 2021), but there is also a strong affectiveemotional basis, revolving around feelings of worry, anxiety, frustration, and anger (Wahlström et al, 2019;de Moor et al, 2020), and a perceived moral duty to act (Fernandes-Jesus et al, 2020;Wallis and Loy, 2021). Social expression and self-signaling, identification, and event enjoyment also play a role (Walgrave et al, 2012;Fernandes-Jesus et al, 2020;Wallis and Loy, 2021;Cologna et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…It could be shown that older people demonstrate out of solidarity, while the younger generation takes to the streets for their own interests (Wahlström et al, 2019;Gardner and Neuber, 2021). Also, feelings such as fear, concern and anger (Wahlström et al, 2019;Gardner and Neuber, 2021), but also hope (Gardner and Neuber, 2021), fun (Cologna et al, 2021), the perceived activism of the social environment (Wallis and Loy, 2021) and political orientation (Cologna et al, 2021;Soliev et al, 2021;Svensson and Wahlström, 2021), as well as social self-efficacy (Cologna et al, 2021;Wallis and Loy, 2021) and efficacy on a collective level (Wallis and Loy, 2021), could be identified as motives and predictors, although the results on efficacy are not clear (Prendergast et al, 2021). However, while protesters have faith in science (Cologna et al, 2021), they express a certain skepticism toward both companies and governments about their ability and willingness to tackle the climate crisis (Wahlström et al, 2019;de Moor et al, 2020;Cologna et al, 2021;Mundaca et al, 2022;Noth and Tonzer, 2022).…”
Section: Introductionmentioning
confidence: 99%